Highly selective amperometric biosensor for uric acid determination in real samples - Zinchenko, O.A.; Shkotova, L.V.; Kulynych, T.U.; Zinkina, O.O.; Soldatkin, A.P. (Вiopolymers and Cell, 2017)
Aim. To develop an amperometric biosensor based on immobilized uricase (1.7.3.3) from Arthrobacter Globiformis and a platinum disk electrode for the detection of uric acid in biological fluids. Methods. To obtain a highly selective detection of the uric acid concentration, an additive semi-permeable polymer film was formed on the surface of a platinum disk electrode by electro-polymerisation of m-phenylene diamine. The enzymatic selective layer was formed on the poly-m-phenylene diamine membrane using uricase immobilized in BSA matrix by a non-toxic crosslinking agent – poly(ethylene glycol) diglycidyl ether (PEGDE). Results. An influence of possible interfering substances – ascorbic acid, cysteine, urea, glucose, glutamic acid and lactic acid – was studied. Almost no effect of these electrochemical compounds on the biosensor response was found, indicating that the selectivity of the developed biosensor is very high. The biosensor characteristics were determined: detection limit 0.001 mM (s/n = 3), linear working range 0.008–0.218 mM, sensitivity 165 μA·mM⁻¹ cm⁻². The biosensor stability and reproducibility were studied and shown. Conclusions. The developed biosensor was validated by comparing the results of the urine samples analysis provided with the biosensor and the spectrophotometric method (correlation coefficient r = 0.99).This biosensor is found to be promising method for uric acid detection in the real samples.